Overexpression of MpCYS4, A Phytocystatin Gene from Malus prunifolia (Willd.) Borkh., Enhances Stomatal Closure to Confer Drought Tolerance in Transgenic Arabidopsis and Apple - Tan, Yanxiao; Li, Mingjun; Yang, Yingli; Sun, Xun; Wang, Na; Liang, Bowen; Ma, Fengwang (Frontiers in Plant Science, 2017)
Phytocystatins (PhyCys) comprise a group of inhibitors for cysteine proteinases in plants. They play a wide range of important roles in regulating endogenous processes and protecting plants against various environmental stresses, but the underlying mechanisms remain largely unknown. Here, we detailed the biological functions of MpCYS4, a member of cystatin genes isolated from Malus prunifolia. This gene was activated under water deficit, heat (40°C), exogenous abscisic acid (ABA), or methyl viologen (MV) (Tan et al., 2014a). At cellular level, MpCYS4 protein was found to be localized in the nucleus, cytoplasm, and plasma membrane of onion epidermal cells. Recombinant MpCYS4 cystatin expressed in Escherichia coli was purified and it exhibited cysteine protease inhibitor activity. Transgenic overexpression of MpCYS4 in Arabidopsis (Arabidopsis thaliana) and apple (Malus domestica) led to ABA hypersensitivity and series of ABA-associated phenotypes, such as enhanced ABA-induced stomatal closing, altered expression of many ABA/stress-responsive genes, and enhanced drought tolerance. Taken together, our results demonstrate that MpCYS4 is involved in ABA-mediated stress signal transduction and confers drought tolerance at least in part by enhancing stomatal closure and up-regulating the transcriptional levels of ABA- and drought-related genes. These findings provide new insights into the molecular mechanisms by which phytocystatins influence plant growth, development, and tolerance to stress.